Hadzabe’s Transformation and Livelihood Dynamics: Livelihood Sustainability in the Changing Environment of Yaeda Valley - Joachim, Luhalala; Zahor, Zahor (Tanzania Journal for Population studies and Development, 2022)
This article aims to document the transformation processes that underlie Hadzabes’ foraging system and their implications on their livelihood. A transect-walk study method used targeting 303 households Hadzabe-foragers. Data was collected using household surveys, interviews, FGDs, observation, documentary reviews and community mapping. Analysis of data was done using SPSS (Version 20) and regression analysis. Land use changes were assessed based on change detection in ArcGIS (Version 10.5). Pareto analysis of the 80-20 principle was used to analyse changes that have occurred to the Hadzabe living system. Findings show that 74% of the participants admitted that change is being caused by development in tourism, change in climate, and population increase. Others are policies, laws and acts on resource use and education. Dynamics in Hadzabe were reported to be taking place slowly via agricultural activities, tourism, trade, beekeeping and poultry. Findings also indicate that, with changes, livelihood sustainability is still a problem requiring stakeholders’ cooperation to solve since the environment continues to change. The study concludes that although the stated causes and dynamics have had significant contributions in transforming the Hadzabe, livelihood sustainability is still a challenge as the Hadzabe continue to disengage from foraging by adopting new economies that ensure livelihood sustainability, while living in a changing environment of marginal and shrinking land. Thus, the community should be sensitized on food security so as to develop strategies to handle food storage for future use, especially during adverse weather conditions.